PIRANTI KOHESI GRAMATIKAL DAN LEKSIKAL PADA WACANA RUBRIK "SELEBRITAS" DALAM MAJALAH FEMINA SEBAGAI BAHAN AJAR MENULIS TEKS NARASI - Septianingrum, Nila Prima; Sabardila, Atiqa (Jurnal Penelitian Humaniora, 2017)
The purpose of this study are (1) describes the use of grammatical cohesion devices in the rubric "Selebritas" in the Feminamagazine; (2) describes the use of lexical cohesion devices in the rubric "Selebritas" in the Femina magazine; and (3) implement the use of grammatical and lexical cohesion devices in rubric "Selebritas" in Femina magazine as one of the teaching material to write narrative texts. The results of this study were (1) grammatical cohesion devices analyzed in this study consisted of 10 reference, 6 conjunction, 3substitution, and 3 ellipsis. Counterfeit reference cohesion divided into 7 reference persona, 2 demonstrative reference and 1 comparative reference. Reference persona is divided into 1 pronoun first person singular, 1 pronoun first personplural, 4 pronouns third person singular, and 1 pronouns third person plural; (2) lexical cohesion devices analyzed in this study consisted of 7 equivalence, 2 hyponymy, 2antonym, 2 repetition, 1 synonymy and 1 collocation; and (3) the results of this research are used as teaching material in high school students of class VII in accordance with Curriculum 2013. These teaching materials can be applied to core competencies 4 and basic competence 4.5.1 which students were asked to compile a narrative text.